Type 2 Diabetes Coagulopathy Proteins May Conflict With Biomarkers Reflective of COVID-19 Severity - Moin, Abu Saleh Md; Al-Qaissi, Ahmed; Sathyapalan, Thozhukat; Atkin, Stephen L.; Butler, Alexandra E. (Frontiers in Endocrinology, 2021)
Objective: Detailed proteomic analysis in a cohort of patients with differing severity of COVID-19 disease identified biomarkers within the complement and coagulation cascades as biomarkers for disease severity has been reported; however, it is unclear if these proteins differ sufficiently from other conditions to be considered as biomarkers. Methods: A prospective, parallel study in T2D(n=23) and controls(n=23). A hyperinsulinemic clamp was performed and normoglycemia induced in T2D (4.5±0.07mmol/l(81±1.2mg/dl) for 1-hour, following which blood glucose was decreased to ≤2.0 mmol/L(36mg/dl). Proteomic analysis for the complement and coagulation cascades were measured using Slow Off-rate Modified Aptamer (SOMA)-scan. Results: 34 proteins were measured. At baseline, 4 of 18 were found to differ in T2D versus controls for platelet degranulation (Neutrophil-activating peptide-2(p=0.014), Thrombospondin-1(p=0.012), Platelet factor-4(p=0.007) and Kininogen-1(p=0.05), whilst 3 of 16 proteins differed for complement and coagulation cascades (Coagulation factor IX (p<0.05), Kininogen-1(p=0.05) and Heparin cofactor-2(p=0.007); STRING analysis demonstrated the close relationship of these proteins to one another. Induced euglycemia in T2D showed no protein changes versus baseline. At hypoglycemia, however, 4 proteins changed in controls from baseline (Thrombospondin-1 (p<0.014), platelet factor-4(p<0.01), Platelet basic protein(p<0.008) and Vitamin K-dependent protein-C(p<0.00003)), and 1 protein changed in T2D (Vitamin K-dependent protein-C, (p<0.0002)). Conclusion: 7 of 34 proteins suggested to be biomarkers of COVID-19 severity within the platelet degranulation and complement and coagulation cascades differed in T2D versus controls, with further changes occurring at hypoglycemia, suggesting that validation of these biomarkers is critical. It is unclear if these protein changes in T2D may predict worse COVID-19 disease for these patients.